Nagari Surantih Kecamatan Batang Kapas Kabupaten Pesisir Selatan Pada Masa Pemerintahan Desa Tahun 1983-2001 - Nofia, Hyeni Roza; Sabar, Sabar; Witrianto, Witrianto (Pendidikan Sejarah, 2013)
ABSTRACTÂ This article purpose of describing the process of forming some villages in Surantih while government system in 1983-2001, and the process of cultural leadership in Surantih since 1983 to 2001, and also about the response of Surantih villagers about village leadership in SurantihThe method which is used in this article is historical method: Heuristic( collecting all sources which is needed), source critic, then fact interpretation, andÂ it was made in scientist a written way called Histiografy.The result of survey shows that first, in forming the village parliament, Surantih consist of 13 villages, they are: Pasar Surantih, Pasir nan panjang, Sungai Sirah, Gunung Malelo, Rawang, Timbulun, Koto Panjang, Koto Marapak, Kayu Gadang, Ampalu, Kayu Aro, Batu Balah, and Langgai. Second, in forming the village parliament, the effect of law implementation in village parliament made the strength and wise of Niniak Mamak decrease for village, the leadership of Niniak Mamak got downing neither Kemenakan nor other villagers. Third, village parliament system was not so easy to do because it was faced by some basic changing in Minangkabau Cultural with the Nagari system which is exposing aspiration from low side to upper. Meanwhile, in village parliament system was focusing in upper instruction, so that made contradictory between them. The conclusion of this survey that, the village parliament system based on law no 5 1979 in Surantih was not running well like what we wished, because of facing of villagerâs ethnic and cultural which was the basic of Minangkabau villager who exposing the aspiration from lower side to upper side.Â Keyword : Nagari, transformatif village